(untitled) (Hoboken, N.J., 2007)
The second volume of the Wiley series, Environmentally Conscious Manufacturing focuses on environmentally preferable approaches to manufacturing. Contributors present and discuss the technologies engineers need to specify and employ to make manufacturing operations environmentally friendly and conform to environmental regulations. Chapters cover Hazardous Waste Minimization and Management; Cost-Effective Manufacturing; Real-time Process Monitoring and Control; Ethics in ECM; Governmental Regulations and Policies, and Total Quality Management. In each chapter case studies are provided to guide readers in areas outside their expertise.
Keywords: Manufacturing processes; Environmental aspects